2000
DOI: 10.1002/1097-4644(20000901)78:3<476::aid-jcb12>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for bone formation: In vitro and in vivo osteogenic activity of an adenovirus expressing BMP7

Abstract: Bone morphogenetic proteins (BMPs) are well-established agents for inducing orthotopic and ectopic bone formation. However, their clinical usefulness as regenerative agents may be limited by a short in vivo half-life and low specific activity. BMP gene therapy is an alternative route for exploiting the bone-inductive activity of this class of molecules. To test the feasibility of this approach, we examined the osteogenic activity of AdCMV-BMP7, an adenovirus containing BMP7 cDNA under control of the CMV promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(125 citation statements)
references
References 37 publications
4
119
0
2
Order By: Relevance
“…Therefore, gene therapy is an alternative route for exploiting the boneinductive activity of this class of molecules. 173 In gene therapy, genes coding for the production of specific proteins are delivered to cells via a virus vector (i.e., retrovirus, adenovirus, adeno-associated virus, herpesvirus), or via non-viral delivery (i.e., naked DNA, oligonucleotides, lipoplexes). The most effective delivery system depends on the application.…”
Section: Chemical Effectors In Synthetic Bone Scaffoldsmentioning
confidence: 99%
“…Therefore, gene therapy is an alternative route for exploiting the boneinductive activity of this class of molecules. 173 In gene therapy, genes coding for the production of specific proteins are delivered to cells via a virus vector (i.e., retrovirus, adenovirus, adeno-associated virus, herpesvirus), or via non-viral delivery (i.e., naked DNA, oligonucleotides, lipoplexes). The most effective delivery system depends on the application.…”
Section: Chemical Effectors In Synthetic Bone Scaffoldsmentioning
confidence: 99%
“…[25][26][27] In addition to the direct application of recombinant BMP proteins, numerous reports have confirmed the ability of adenoviral or retroviral vector-mediated gene transfer of several BMPs to induce bone formation in animal models. 18,20,21,23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Although a plethora of studies have demonstrated the ability of several BMPs, mostly BMP-2 and BMP-7, to promote osteogenesis, it is unclear whether or not BMPs other than those currently being tested in clinical trials are more potent stimulators of new bone formation. Thus, it is important to conduct a comprehensive comparative analysis of the in vivo osteogenic activity of all BMPs.…”
Section: Introductionmentioning
confidence: 99%
“…The BMP viral vectors include recombinant adenovirus, retrovirus and baculovirus. 13,[28][29][30][31][32][33] Gysin et al 34 demonstrated that recombinant BMP-4 retrovirus-transduced stromal cells embedded in a gelatin matrix could heal critical size defects in calvariae of syngeneic rats. Gelatin matrices without cells and with untransduced stromal cells were the two control groups.…”
Section: Introductionmentioning
confidence: 99%
“…In both locations, an ossicle containing cortical and trabecular bone and a clearly defined marrow cavity formed at the site of virus implantation within 4 weeks. 32 Recombinant BMP-9 adenoviruses, which include both first-generation and helper-dependent adenoviral vectors, induced the ectopic bone formation in both athymic nude rats and Sprague-Dawley rats. 11,13,39 Since different BMP adenoviral vector doses and different animal models were used in previous studies, it remains unclear which BMP vector has the highest potential to stimulate bone formation.…”
Section: Introductionmentioning
confidence: 99%